2010
DOI: 10.1007/s13105-010-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL and its correlation with lipid profile and oxidative stress biomarkers in young healthy Spanish subjects

Abstract: The biological effects of oxidized LDL (oxLDL) may contribute to initiation and progression of the atherosclerotic process, and the association between cardiovascular disease and oxidation of LDL has been largely demonstrated. The objectives of this study were to establish the reference values of oxidative stress biomarkers in a young healthy Spanish population to determine the concentration of oxLDL and its relationship with lipid profile and with these biomarkers. oxLDL, F(2)-isoprostanes, protein carbonyls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
4
16
2
Order By: Relevance
“…On the other hand, Koubaa et al [39] did not find any difference in ox-LDL levels among Tunisian carriers of the C677T variant allele. The mean ox-LDL concentrations verified in our study were lower than those observed in adolescents and young adults with severe obesity and greater oxidative stress degree [40,41]. …”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, Koubaa et al [39] did not find any difference in ox-LDL levels among Tunisian carriers of the C677T variant allele. The mean ox-LDL concentrations verified in our study were lower than those observed in adolescents and young adults with severe obesity and greater oxidative stress degree [40,41]. …”
Section: Discussioncontrasting
confidence: 52%
“…A positive correlation of OxLDL concentration with cholesterol levels and body mass index, has been reported in previous studies [30,33,37] indicating that metabolic syndrome and their components as obesity exacerbates oxidized LDL levels in a feedback loop [39]. The results found in the corroborates the relevance of oxidative stress status on OxLDL levels.…”
Section: Discussionsupporting
confidence: 81%
“…These results are not new since a large body of previous evidences has described the influence of obesity on lipid, oxidative and inflammatory biomarkers [30,36,37]. However, in our study we found that the alterations in these biomarkers can be influenced by the genetic status of volunteers considering the Ala16Val MnSOD polymorphism.…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed small LDL particles themselves are easily oxidized to yield atherogenic oxidized LDL (ox-LDL) particles, also detectable in healthy subjects [5, 6]. Elevated levels of ox-LDL particles in blood stream have been reported to be associated with increased cardiovascular disease risk [6, 7]. …”
Section: Introductionmentioning
confidence: 99%